INTERPLEURAL ANALGESIA AFTER SURGERY INTERVENTIONS ON THE VERTEBRAL COLUMN IN TUBERCULOUS SPONDYLITIS PATIENTS - O. N. Pulkina; G. E. Ulrich; D. V. Kuklin; V. M. Bragilevsky (Вестник анестезиологии и реаниматологии)
Goal of the trial: to evaluate efficiency interpleural administration of local anesthetics for pain management after surgery on the thoracic spine. Materials and methods. Tuberculosis spondylitis patients after the surgery on the thoracic spine were divided into two groups depending on the way of postoperative anesthesia. Interpleural administration of local anesthetic was used for the 1st group, and drug therapy was used for the 2nd group. Every 4 hours of the postoperative period the pain intensiveness, non-invasive hemodynamic monitoring, the quantity of used analgesics, activeness of patients and side effects such as nausea and vomit were evaluated as per the visual analogous score. Results. Interpleural block after thoracic spine surgery in tuberculosis spondylitis patients statistically significantly reduces the pain intensiveness, quantity of taken analgesics and their side effects, increases the activity of patients comparing to the patients who had analgesics administered parenterally. Conclusion. The trial proves the efficiency and safety of interpleural analgesia for postoperative pain management after surgery on the thoracic spine.